Analisa Kinerja Keuangan PT Garuda Indonesia (TBK) Sebagai Langkah Awal Identifikasi Permasalahan - Chandrayanti, Teti; Salfadri, Salfadri; Haryati, Rice (MAMEN: Jurnal Manajemen, 2022)
PT Garuda Indonesia is a state-owned company that has recently experienced complex problems. Prolonged problems put PT Garuda's condition on the verge of bankruptcy. This research was conducted using 2 financial statements, namely the Financial Position Statement (Balance Sheet) and the Financial Statement of Profit and Loss for the Period 2019 and 2020. Based on the financial position report (balance sheet), it shows that starting from Q4 2019, there has been a negative recording of equity, this means that the amount of loans exceeds the amount of owned capital, with a significant increase in long-term loans. The income statement shows that in 2019 starting from the 2nd quarter there has been a decrease in profit after tax, even in Q1 of 2020, it has been recorded that the company has a loss. Restrictions on mobility and activities due to the Covid-19 pandemic have caused the company's revenue to decline. In 2019-2020, there began to be signs of financial problems detected from the balance sheet financial statements and income statements. Furthermore, alternative solutions related to debt restructuring and also company restructuring and also comparative analysis with similar industries that have experienced relatively similar problems were proposed.